Present status and prospects of technical development of tuna sea-farming - Lioka C.; Kani K.; Nhhala H. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
Because its large size, excellent taste and high market price Bluefin tuna is one of the most important species in fisheries. Besides appropriate utilization and management of tuna resources, it is necessary to promote the adequate aquaculture technologies. In 1970, an experiment of rearing bluefin tuna was started in Japan. At present, the culture and seed production experiments are conducted by the different institutions and private companies. Although, about hundred yearlings were released by the national sea-farming center in 1998, mass seed production has not yet been succeeded. In order to establish seed production technologies of bluefin tuna, it is necessary to resolve many problems. At present technical problems include: (i) development of broodstock rearing technology; (ii) solution of broodstock mature mechanism; (iii) development of initial-stage larvae feed; (iv) improvement of larvae and fry survival rate; and (v) development of seed release technology.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)